Anatase Film on Orotracheal Tubes to Mitigate Staphylococcus aureus - Manfroi, Lucas Augusto (2022)
Bacterial contamination in hospital environments is a significant concern for patient admissions. Aiming to reduce contamination, titanium dioxide film (TiO2) in the anatase phase has been prepared on the surface of polyvinyl chloride (PVC) tubes. The PVC tube material was used to study the film's effectiveness in inhibit-ing bacterial growth and cell viability. The morphology and composition of deposited films were investigated using a Scanning Electron Microscope (SEM) and Energy Dispersive Spectroscopy (EDS) map. In addition, Fourier-Transform Infrared Spectroscopy (FTIR) and XRD diffractogram were used to analyze film composition and phase, respectively. The adhesion of TiO2 film on PVC substrate was determined using ScotchTM tape-test according to ASTM: D3359-09,IP: 2010,and203.8.109.20the filmOn: Wed,surface 01 morFeb phology2023 was16:21:47analyzed by the MEV-FEG tech-nique and EDS map. The bacterial viability was performed with Staphylococcus aureus, and cell viability was Copyright: American Scientific Publishers performed using L929 strain mouse fibroblasts. The results of TiO2 in the anatase phase deposited by ALD Delivered by Ingenta on the PVC surface demonstrate good adherence and the film's effectiveness in inhibiting bacterial growth and cell viability.